Realists Still Divided by Realism? Response to Wright. Issue 2 (14th March 2016) - Morgan, Jamie
Abstract : In this short paper I reply to Wright's response to my original essay on his Christianity and Critical Realism . Wright makes a number of important points, and these are interesting in so far as they indicate how the same issues can be read in quite different ways. However, this difference ultimately highlights the central issue I explore in the original essay. That is, the capacity for basic dividing lines to occur and persist because of the fundamental nature of the issues at stake.